Different Munc13 Isoforms Function as Priming Factors in Lytic Granule Release from Murine Cytotoxic T Lymphocytes. (9th May 2013) - Dudenhöffer‐Pfeifer, Monika; Schirra, Claudia; Pattu, Varsha; Halimani, Mahantappa; Maier‐Peuschel, Monika; Marshall, Misty R.; Matti, Ulf; Becherer, Ute; Dirks, Jan; Jung, Martin; Lipp, Peter; Hoth, Markus; et al.
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>